Impact of Type 2 Diabetes Mellitus on Pulmonary Function Tests - Abdulsaid , Ruaa; Sajid, Azza; Kadhim Akar , Talib (Iraqi Journal of Pharmaceutical Sciences, 2023)
Background: Diabetes mellitus is a chronic metabolic disorder that may affect different organs including the lungs. Different studies have been published on the effects of diabetes mellitus on pulmonary function. A restrictive pattern of lung disorder was reported in some studies, whereas an obstructive pattern was suggested in others. The study aims to determine the impact of type 2 diabetes on pulmonary function tests (PFTs) and the type of respiratory disorder. Material and Methods: This observational study was conducted in Basrah City, Iraq. One hundred and eighty-two participants were enrolled and divided into 2 groups: 100 healthy (group1) and 82 patients with type2 diabetes mellitus (group 2).PFTs were estimated by a medical spirometer and measurements of several hematological tests were done for each individual. Results: We found a significant decline (p >0.05) in each of FEV1, FVC, PEF, and MVV and a significant increase in ELA in group 2. The restrictive pulmonary disorder was a higher percentage (24.39%) than obstruction (10.9%) and combined (2.43%). Conclusion: Pulmonary function tests were significantly affected by type2 DM and the percentages of different respiratory disorders were higher among group 2 than in group 1, with an increase in restrictive pattern.